(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Concurrent chemoradiotherapy with or without induction chemotherapy is widely practiced in inoperable stage III and IVA/B head and neck cancer. The aim of this study was to investigate the survival and toxicity outcomes of induction chemotherapy combined with concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in inoperable stage III and IVA/B head and neck cancer patients. From June 2018 to July 2020, 86 patients participated in a quasi-experimental study. Patients were purposively assigned to one of the two arms (arm A or arm B). Arm A got induction chemotherapy and concurrent chemo- radiotherapy, while arm B got only concurrent chemoradiotherapy. According to our findings, the 2-year progression-free survival rate in arm A was 48.8% vs 37.2 % in arm B (p-value=0.042), and the 2-year overall survival rate in arm A was 65.1 % versus 60.5 % in arm B (p-value= 0.416). There were no statistically significant variations in treatment-related toxicities between the two groups (p-value > 0.05). In conclusion, inoperable stage III and IVA/B head and neck cancer patients who got induction chemotherapy plus concurrent chemotherapy had a better progression-free survival rate than those who received concur- rent chemoradiotherapy alone. BSMMU J 2021; 14(4): 144-147